2009
DOI: 10.1002/chem.200900042
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Investigation of the Alkyl–Alkyl Negishi Cross‐Coupling Reaction Catalyzed by N‐Heterocyclic Carbene (NHC)–Pd Complexes

Abstract: A novel mechanism is proposed for the Pd-1,3-(2,6-diisopropylphenyl)imidazolyl-2-ylidene (1) catalyzed Negishi reaction. DFT computations supported by atoms-in-molecules (AIM) analyses of non-truncated models show that a "steric wall" created by the N-substituent on the ligand guides reactants to and from the Pd center. Notably, transmetalation and not oxidative addition is found to be rate-limiting. Additionally, a key Pd-Zn interaction (approximately = 2.4 A, rho(b) approximately = 0.0600 au) is identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 84 publications
3
39
0
1
Order By: Relevance
“…Unexpectedly, complexes that had previously proven inactive (9)(10)(11)(12)(13)(14) were able to generate significant cross-coupled product, which perhaps indicates that something unique occurs with aryl organozinc reagents.…”
Section: Wwwchemeurjorgmentioning
confidence: 93%
See 4 more Smart Citations
“…Unexpectedly, complexes that had previously proven inactive (9)(10)(11)(12)(13)(14) were able to generate significant cross-coupled product, which perhaps indicates that something unique occurs with aryl organozinc reagents.…”
Section: Wwwchemeurjorgmentioning
confidence: 93%
“…[11,12] have revealed that these species are completely inactive in Negishi reactions and that the active catalyst must therefore be a palladium complex with only one NHC ligand. [9,13,14] With the uncertainty of the in situ protocol in mind, our group [12,15] and others [7,16] embarked on the development of well-defined NHC-Pd precatalysts (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations